Synthesis, Characterization And Catalytic Activity Of Cao-Based Catalysts In Transesterification Of Non-Edible And Waste Cooking Oils Into Glycerol-Free Fatty Acid Methyl Ester - Syamsuddin, Yanna (2017)
Biodiesel, known as fatty acid methyl ester (FAME), has become more interesting as an alternative fuel due to its renewability and low emissions. The synthesis of biodiesel was conducted via transesterification using dimethyl carbonate (DMC) over heterogeneous catalyst to overcome over production of glycerol and to avoid the use of huge wastewater for purification process. The aim of this study is to develop an active, stable and reusable heterogeneous catalyst for transesterification of non-edible vegetable oils and waste cooking oil with DMC to produce glycerol-free FAME. The CaO-based mixed-oxide catalysts (Ca‒Zn, Ca‒La and Ca‒La‒Al) were synthesized by co-precipitation method followed by calcination at various temperature of 300 oC to 900 oC and time of 1 to 5 h. The physicochemical properties of catalysts were characterized by the Thermal Gravimetric Analyze (TGA), N2 adsorption-desorption isotherm, X-ray Diffraction (XRD), Fourier Transformed Infra Red (FTIR), Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX) and Temperature Program Desorption (TPD) analysis. Catalysts performances were evaluated on transesterification reaction using a batch process at various operating condition, that include temperature (110-190 oC), reaction time (30-360 min), DMC-to-oil molar ratio (2:1-18:1) and amount of catalyst loading (1-13 wt.%, based on oil weight). Results revealed that Ca‒Zn catalyst has good catalytic activity for transesterification of low and moderate FFA content vegetable oils. The catalyst can be reused only for two cycles of reaction for transesterification of jatropha oil. The Ca‒La catalyst showed better performance; it can catalyzed four different types of oil except waste cooking oil and can be reused up to five reaction cycles. The Ca‒La‒Al catalyst confessed good performance for all five oils with the highest FAME content ≥ 96.5% at various best operating conditions, such as temperature of 150-170 oC, reaction time of 180 min for non-edible oils and 300 min for Waste Cooking Oil (WCO), DMC-to-oil molar ratio of 9:1 for Crude Karanj Oil (CKO) and Crude Palm Kernel Oil (CPKO) and 15:1 for Crude Jatropha Oil (CJO), Crude Palm Oil (CPO) and WCO, amount of catalyst loading of 5-7 wt.% for CJO, CKO and CPKO and 10 wt% for CPO and WCO, and reusable for 4-5 reaction cycles. The kinetic study revealed that the transesterification of all oils with DMC were fit to pseudo-first order reaction with the average rate constant (k) of 0.0067/min, 0.013/min, 0.011/min, 0.0067/min and 0.0087/min for CJO, CKO, CPKO, CPO and WCO, respectively. The activation energy was in the range of 29.2-82.2 kJ/mol. It can be concluded that the Ca‒La‒Al catalyst was a potential solid catalyst for a new route of transesterification reaction of various Free Fatty Acid (FFA) content vegetable oils to produce glycerol-free FAME.